ابن قیم ؒ کی کتاب زاد المعاد :تعارف، منہج واسلوب اور امتیازی خصوصیات (Al-Qamar, 2021)
The beginning of the writing of books on the biography of the Prophet ﷺ started from the first century, in which a trend of excess was found day by day, until now millions of books have been written on the subject of the biography of Prophetﷺ  . And they are still being written and will continue to be written in the future. There are some books which have been accepted in the Islamic Ummah due to their special qualities. Among them is a book by Ibn Qayyim, Zaad al-Ma'ad. Ibn Qayyim is a famous researcher and scholar of the seventh century. You have written this book on the subject of biography, in which you have written this book covering all the existing aspects and dimensions of biography. So you have studied the Holy Quran, blessed hadiths, jurisprudence, grammar, Arabic vocabulary, and Poems are mentioned in a coherent manner in the biography of the Prophet (peace be upon him). Therefore, in this article, this book will be briefly mentioned in an analytical manner.
Keywords: Ibn Qayyim; Zad al-Maʻad; Prophet's biography; Manhāj; Fiqh